Asosiasi Jaminan Sosial dengan Partisipasi Kerja Penduduk Lansia di Indonesia - Wibowo, Evelyn Fairuz; Handayani, Dwini (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
Indonesia has entered a period of aging population. The number of elderly people has increased sharply without social security ownership, making the elderly population vulnerable to poverty. Financial demands make the elderly must continue to work in their old age, even though their biological and psychological conditions are declining. The study aims to analyzes the effect of social insurance (pension insurance and health insurance) on the work participation of the elderly population which is controlled based on individual, household, and social characteristics. Using secondary data from the 2020 National Socioeconomic Survey and analyzed using logistic biner regression, this study found that the ownership of pension security and health insurance has a significant negative effect on the work participation of the elderly. Elderly people who are heads of households, have low education, male, live in rural areas, have no health problems, have a large number of working family members, and whose economic conditions are below the poverty line tend to continue working at retirement age.